Вплив електронних станів нанографенів у вуглецевих мікрокристалітах на хімію поверхні різновидів активного вугілля - Стрелко, В.В.; Горлов, Ю.І. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2021)
In this paper, the nature of the chemical activity of pyrolyzed nanostructured carbon materials (PNCM), in particular active carbon (AC), in reactions of electron transfer considered from a single position, reflecting the priority role of paramagnetic centers and edge defunctionaled carbon atoms of carbon microcristallites (CMC) due to pyrolysis of precursors. Clusters in the form of polycyclic aromatic hydrocarbons with open (OES) and closed (CES) electronic shells containing terminal hydrogen atoms (or their vacancies) and different terminal functional groups depending on specific model reactions of radical recombination, combination, replacement and elimination were used to model of nanographenes (NG) and CM. Quantum-chemical calculations of molecular models of NG and CMC and heat effects of model reactions were performed in frames of the density functional theory (DFT) using extended valence-splitted basis 6-31G(d) with full geometry optimization of concrete molecules, ions, radicals and NG models. The energies of boundary orbitals were calculated by means of the restricted Hartry-Fock method for objects with closed (RHF) and open (ROHF) electronic shells. The total energies of small negative ions (HOO-, HO-) and anion-radical О2•‾) were given as the sum of calculated total energies of these compounds and their experimental electron affinities. The estimation of probability of considered chemical transformations was carried out on the base on the well-known Bell-Evans-Polyani principle about the inverse correlation of the thermal effects of reactions and its activation energies. It is shown that the energy gap ΔЕ (energy difference of boundary orbitals levels) in simulated nanographens should depend on a number of factors: the periphery structure of models, its size and shape, the number and nature of various structural defects, electronic states of NG. When considering possible chemical transformations on the AC surface, rectangular models of NG were used, for which the simple classification by type and number of edge structural elements of the carbon lattice was proposed. Quantum chemical calculations of molecular models of NG and CNC and the energy of model reactions in frames of DTF showed that the chemisorption of free radicals (3O2 and N•O), as recombination at free radical centers (FRC), should occur with significant heat effects. Such calculations give reason to believe that FRC play an important role in formation of the functional cover on the periphery of NG in CMC of studied materials. On the base of of cluster models of active carbon with OES new ideas about possible reactions mechanisms of radical-anion О2•‾ formation and decomposition of hydrogen peroxide on the surface of active carbon are offered. Explanation of increased activity of AC reduced by hydrogen in H2O2 decomposition is given. It is shown that these PNCM models, as first of all AC, allow to adequately describe their semiconductor nature and acid-base properties of such materials.